Analysis of social development in the Arctic countries. Issue 1 (September 2020) - Kikkas, K N
Abstract: The paper describes features of the development of the social sphere of the Arctic countries. Almost four million people live in the Arctic. The Arctic includes part of the territories of eight countries: Canada, Denmark, Finland, Iceland, Norway, Russia, Sweden and the United States of America. The Arctic is also home to dozens of indigenous groups. To develop strategies for the development of the Arctic territories, it is important to compare the features of the development of the social sphere of the Arctic countries. The paper provides a list of indicators evaluating the development of the social sphere. The methodology of a comparative analysis of the convergence or divergence of indicators of the social sphere of eight Arctic countries is described. An analysis of the existence of convergence / divergence of indicators of the social sphere is carried out. The analysis was carried out using three methods: σ – convergence; absolute β – convergence; conditional β – convergence. The results of the analysis are discussed.